The association between infectious burden and Parkinson's disease: A case-control study. Issue 8 (August 2015) - Bu, Xian-Le; Wang, Xin; Xiang, Yang; Shen, Lin-Lin; Wang, Qing-Hua; Liu, Yu-Hui; Jiao, Shu-Sheng; Wang, Ye-Ran; Cao, Hong-Yuan; Yi, Xu; Liu, Cheng-Hui; Deng, Bo; et al.
Abstract Introduction The etiology of Parkinson's disease (PD) remains unclear. The aim of this study was to examine the association between common pathogenic infections and PD. Methods Antibody titers to common infectious pathogens including cytomegalovirus (CMV), Epstein Barr virus (EBV)，herpes simplex virus type-1 (HSV-1), Borrelia burgdorferi (B. burgdorferi), Chlamydophila pneumoniae (C. pneumoniae) and Helicobacter pylori (H. pylori) were measured by ELISA in serum of 131 PD patients and 141 normal controls. Infectious burden (IB) was defined as a composite serologic measure of exposure to these common pathogens. Results Seropositivities toward zero-two, three-four and five-six of these pathogens were found in 11%, 74% and 15% of normal controls while in 4%, 61% and 35% of PD patients, respectively. IB, bacterial burden and viral burden were independently associated with PD. Schwab and England (S&E) scores were negatively correlated with IB in patients with PD. Serum α-synuclein protein levels and inflammatory cytokines (interleukin-1β and interleukin-6) in individuals with higher IB were also significantly higher. Conclusions IB consisting of CMV, EBV, HSV-1, B. burgdorferi, C. pneumoniae and H. pylori is associated with PD. This study supports the role of infection in the etiology of PD.